Refill friction stir spot welding of different thickness Al-Cu alloy using a tool with reduced dimensions for aerospace application - Santos, Murilo Feliciano de Lima (Universidade Federal de São Carlos, 2020)
Refill Friction Stir Spot Welding has grown as an interesting alternative to conventional joining techniques in recent years, especially when it comes to high strength aluminum alloys. Although current results show promise, there are still areas in which the body of knowledge is lacking and there are challenges for further investigation. This work tackled some of those challenges by investigating and optimizing the refill FSSW process for 2A12 (AA2024) aluminum alloy using a tool with reduced dimensions to weld an unconventional sheet configuration (0.8mm to 3mm in thickness). This was achieved using Design of Experiments coupled with Analysis of Variance. In addition, the influence of process parameters on microstructural geometrical features and in weld performance was studied, and Plunge Depth was found to be the most significant process variable when it comes to weld strength. Crack was shown to start around the hook region and propagate through two possible paths, the SZ/TMAZ interface or the aluminum rich layer in the stir zone. These two paths generated two main fracture modes, and the pullout mode was associated with the optimal condition. Given that a 2xxx series aluminum alloy was used, natural aging was investigated, and found to be influential in local mechanical properties through hardness tests. This influence, however, did not translate to Lap Shear Strength, as samples with different aging levels presented similar properties. Finally, the wear behavior of the tool was studied with increasing welding cycles. Tool geometry was significantly affected by wear, and this impacted weld surface with time, generating increasing notches on the edge of the stir zone. Those notches reduced the effective thickness of the top sheet, and consequently contributed to premature failure at inferior loads.
Soldagem a ponto por fricção de liga de Al-Cu de diferentes espessuras utilizando ferramenta com dimensões reduzidas para aplicação aeroespacial
Keywords: Solid state welding; Refill FSSW; 2A12; Design of experiments; ANOVA; Natural aging.; Tool wear; Soldagem no estado sólido; Planejamento de experimentos; Envelhecimento natural; Desgaste de ferramenta; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA